Reforming Child Protection Laws to Secure the Right to Education for Rape Victims - Agustini, Shenti; Febriyani, Emiliya; Hapsari, Autia Kurnia Putri (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
This research emphasizes the urgent need to update legal protections for student rape victims to ensure their right to formal education. Many victims face barriers to education following rape, losing opportunities to continue their studies. This study critically examines the need for legal reform to safeguard their educational rights, focusing on legislative frameworks and provisions. Using a case-based methodology and juridical-normative analysis, the research explores existing legal approaches, such as the General Law No. 12 of 2022 and Government Regulation No. 43 of 2017, which address restitution for child victims of criminal acts. The findings stress the responsibility of educational institutions and stakeholders to uphold education rights for all students, regardless of circumstances. The research contributes to the discourse on restitution, suggesting legal reform to ensure perpetrators cover the costs of education and support for victims, thereby offering a path forward in protecting vulnerable students.